Scientific literature on higher education rankings: a systematic review - Marina Tomàs-Folch; Mònica Feixas Condom; Maria Dolors Bernabeu; José María Ruíz (Universitat Politècnica de València, 2015)
A systematic review of scientific literature on university rankings is presented. This research has focused on the methodology used for the investigators in the reported publications. According to the search criteria 28 articles were included, from social and humanities ISI and Scopus database during the 2000-2012 period. The keywords used were: "rankings", "higher education" and "university". The focus of the analysis was the following criteria:  keywords, publication year, citation references, the subject area, met criteria, geographical scope, research methodology and methods impact of results, language of publication, citation index, impact and assessment of the rankings. The results of the systematic review show that the publications have a more quantitative than qualitative orientation (n=22 vs.  n=6), the approaches are more general than specific (n=21 vs. n=7) and the impact is more generalized than local (n=24 vs. n=4). Moreover, the highest number of the references were published between 2005-2010. We conclude that there is a growing interest and concern for studies focused on the research of university rankings.